وسطية الإسلام فى مجتمع متعدد الثقافات المجتمع الإندونيسي نموذجا - Muhammad Aniq (TAWASUT, 2020)
Abstract Multiculturalism is the cultural diversity of communities within a given society and the policies that promote this diversity. As a descriptive term, multiculturalism is the simple fact of cultural diversity and the demographic make-up of a specific place, sometimes at the organizational leve. As a prescriptive term, multiculturalism encourages ideologies and policies that promote this diversity or its institutionalization. In this sense, multiculturalism is a society “at ease with the rich tapestry of human life and the desire amongst people to express their own identity in the manner they see fit. This paper discusses multicultural ideologies or policies vary widely, ranging from the advocacy of equal respect to the various cultures in a society, to a policy of promoting the maintenance of cultural diversity, to policies in which people of various ethnic and religious groups are addressed by the authorities as defined by the group they belong to. Pluralism, diversity and multiculturalism is a daily fact of life in Indonesia. There are over 300 ethnic groups in Indonesia. The Javanese is the largest ethnic group in Indonesia who make up nearly 42% of the total population. The Sundanese, Malay, and Madurese are the next largest groups in the country. There are also more than 700 living languages spoken in Indonesia and although predominantly Muslim the country also has large Christian and Hindu populations. This paper also uncloses the model of Islamic Moderation in Indonesia societies in the light of Various Cultures and Relegion.